Developing Halal Industry in Indonesia using Interpretive Structural Modeling (ISM) - Rusydiana, Aam Slamet; Mahsyar, Nun Maziyyah (Halal Tourism and Pilgrimage, 2023)
Halal industry has become a popular object and the latest trends in the world of international business. Not only in Indonesia but also Malaysia, Thailand even Europe began to glance at the potential and opportunities for halal industry. The phenomenon that began to develop halal industry in recent years is quite the attention of businesses and consumers themselves. Labeling "halal" or "sharia" on a product, not again become a form of obligation or obedience to a Muslim but has become the strength of a strong market, which not only as a guarantee of the products that are allowed for a Muslim but also a symbol of the global for quality assurance and a lifestyle choice. In previous studies, many researchers were interested in examining issues about the potential of halal industry, while very few researchers discuss the problems of the development of halal industry in Indonesia. Though research on the obstacles and development strategies of halal industry is needed to accelerate the development of halal industry in Indonesia. Based on this problem, which is taken from the study of literature, previous research and indepth interviews with academicians and practitioners, some issues in the development of the halal industry in Indonesia is divided into five aspects: 1) Policy, 2) Production, 3) Socialization, 4) Infrastructure, and 5) Human Resources.